2009
DOI: 10.1177/0002716208324759
|View full text |Cite
|
Sign up to set email alerts
|

Race in the American Mind: From the Moynihan Report to the Obama Candidacy

Abstract: In 1965 Daniel Patrick Moynihan observed that the "racist virus in the American blood stream still afflicts us." The authors assess the tenor of racial attitudes in white and black America across the ensuing four decades. Their core conclusion is paradoxical. On one hand, a massive positive change in social norms regarding race has taken place that dislodged Jim Crow ideology and now calls for integration and equality as the rules that should guide black-white interaction. On the other hand, negative stereotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 38 publications
1
67
0
Order By: Relevance
“…Social scientists have asked whether this change signals a broadening of predominant definitions of cultural membership, as well as a heightened awareness of differentiation among blacks (opposing middle class and ghetto blacks) (e.g. Bobo and Charles, 2009;Kloppenberg, 2010;Sugrue, 2010 African-Americans to belong to this group) and group categorization (the meaning given to this group by out-group members (also Cornell and Hartman, 1997). Hence, understanding responses to stigmatization requires considering the formation of collective identities: how "us" and "them" are mutually defined, and how individuals and groups engage in boundary work in responding to stigmatization, both in private (when they ruminate about past experiences and how to make sense of their experiences), and in public, when they interact with others while reacting to specific events or incidents.…”
Section: Why This Special Issue? Why Now?mentioning
confidence: 99%
“…Social scientists have asked whether this change signals a broadening of predominant definitions of cultural membership, as well as a heightened awareness of differentiation among blacks (opposing middle class and ghetto blacks) (e.g. Bobo and Charles, 2009;Kloppenberg, 2010;Sugrue, 2010 African-Americans to belong to this group) and group categorization (the meaning given to this group by out-group members (also Cornell and Hartman, 1997). Hence, understanding responses to stigmatization requires considering the formation of collective identities: how "us" and "them" are mutually defined, and how individuals and groups engage in boundary work in responding to stigmatization, both in private (when they ruminate about past experiences and how to make sense of their experiences), and in public, when they interact with others while reacting to specific events or incidents.…”
Section: Why This Special Issue? Why Now?mentioning
confidence: 99%
“…Yet, racial inequality persists. The majority of white people in the USA now disagrees with biological racist accounts but also opposes government programmes designed to aid black people and reduce the race gap in income, educational attainment, wealth and other areas (Kluegel 1990;Bobo and Charles 2009). Studies have shown clear evidence of negative attitudes towards black people held by employers, realtors, landlords and bankers (Pager and Quillian 2005;Pager 2007;Pager and Karafin 2009;Roscigno, Karafin and Tester 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with research that addresses the changing ways that prejudices (racism, sexism, and heterosexism) manifest. Specifically, this line of inquiry shows that despite trends toward increased support for equality in the public realm with regard to race, gender, and sexual orientation, there has been less change in the private realm, such as issues of family (Bobo and Charles 2009;England 2010;Morrison et al 2009;Walls 2008). Regression models further showed that variation in the opinions of pro-LGB policies of Nebraskans is largely consistent with subgroup differences in other studies of opinions of LGB policies (Baunach 2012;Becker and Scheufele 2011;Lewis 2011;Pew Research 2013b;Schwartz 2010): males, older people, Republicans, and those who identified as very conservative and born-again Christians were significantly less likely to support LGB civil rights.…”
Section: Discussionmentioning
confidence: 99%